New species for the ant fauna of Slovenia (Hymenoptera: Formicidae) - Gregor Bračko (Natura Sloveniae)
A list of 14 ant species, reported for the first time for the Slovenian fauna, is given, namely: Cryptopone ochracea, Proceratium melinum, Myrmica lonae, Myrmica salina, Aphaenogaster epirotes, Aphaenogaster muelleriana, Leptothorax albipennis, Leptothorax corticalis, Leptothorax crassispinus, Leptothorax exilis, Leptothorax flavicornis, Leptothorax gredleri, Liometopum microcephalum, Formica lusatica. The new ant species were established from recently collected material and after re-examining the material from various collections by considering recent taxonomic revisions. Leptothorax nylanderi should be deleted from the ant list for Slovenia.